Genetic and immunologic features associated with thrombocytopenia progression and poor prognosis in patients with myelofibrosis - Kim, Tong Yoon; Eom, Ki-Seong; Lee, Ji Yoon; Lee, Jong-Mi; Kim, Myungshin; Lee, Sung-Eun (Frontiers in Medicine, 2024)
Introduction Myelofibrosis, which includes primary myelofibrosis (PMF) and secondary myelofibrosis (SMF), can exhibit cytopenic features associated with poor outcomes; however, the underlying mechanisms are unclear. Moreover, characterized by its aggressive nature and limited therapeutic options, myelofibrosis poses a major clinical challenge in hematology. Therefore, in this study, we aimed to identify genetic and immunologic features associated with thrombocytopenia progression and poor prognosis. Methods The study involved 226 patients with PMF or SMF, who were categorized into three groups: platelet count ≥ 100 × 109/L (PLT ≥ 100 group; n = 131), progression to thrombocytopenia (PROG group; n = 64), and platelet count < 100 × 109/L (PLT < 100 group; n = 31). Results Survival analysis revealed 4-year overall survival rate of 57.7%, 89.4%, and 93.9% for the PLT < 100, PROG, and PLT ≥ 100 groups, respectively. Time-dependent covariate analysis of the PLT ≥ 100 and PROG groups revealed inferior overall survival rate of the PROG group. Multivariate analysis indicated that progression to thrombocytopenia and ASXL1 and IDH1 mutations were associated with poor overall survival. Flow cytometry revealed fewer CD45RA+CD4+ T cells in the PROG group than in the PLT ≥ 100 group. ASXL1 mutations were more prevalent in the PROG group than in the other groups, correlating with a reduced number of CD45RA+CD4+ T cells. Discussion ASXL1 mutation and low CD45RA+CD4+ T-cell counts correlated with progression to thrombocytopenia. Our findings underscore the clinical significance of thrombocytopenia dynamics in MF progression and prognosis, with implications for patient management and therapeutic interventions.